Causes and risk factors for absenteeism among medical staff in german specialized lung clinics during the COVID pandemic - Piel, Stella; Presotto, Maria Ada; Jörres, Rudolf A.; Karrasch, Stefan; Gesierich, Wolfgang; Bullwinkel, Jörn; Rabe, Klaus F.; Hayden, Markus C.; Kaestner, Franziska; Harzheim, Dominik; Joves, Biljana; Kempa, Axel T.; et al. (Respiration, 2023)
Background: Staff shortages pose a major challenge to the health system. Objectives: The objective of this study was to clarify the role of different causative factors we investigated on staff absenteeism during the COVID pandemic. Methods: The prospective multicentre cohort study assessed the private and professional impact of the pandemic on health care workers (HCWs) using a specially developed questionnaire. HCWs from 7 specialist lung clinics throughout Germany were surveyed from December 1 to December 23, 2021. The current analysis addresses pandemic-related absenteeism. Results: 1,134 HCW (55% female; 18.4% male, 26.3% not willing to provide information on age or gender) participated. 72.8% had received at least one vaccination dose at the time of the survey, and 9.4% reported a COVID infection. Of those with positive tests, 98% reported home quarantine for median (IQR) 14 (12-17) days; 10.3% of those who ultimately tested negative also reported quarantine periods of 14 (7-14) days. 32.2% of vaccinated respondents reported absenteeism due to vaccine reactions of 2 (1-3) days. Overall, 37% (n = 420) of HCW reported pandemic-related absenteeism, with 3,524 total days of absenteeism, of which 2,828 were due to illness/quarantine and 696 to vaccination effects. Independent risk factors for COVID-related absenteeism ≥5 days included already having COVID, but also concern about long-term effects of COVID (OR 1,782, p = 0.014); risk factors for vaccine-related absenteeism ≥2 days included concerns of late effects of vaccination (OR 2.2, 95% CI: 1.4-3.1, p < 0.000). Conclusion: Staff shortages due to quarantine or infections and vaccine reactogenicity have put a strain on German respiratory specialists. The fact that staff concerns also contributed to absenteeism may be helpful in managing future pandemic events to minimize staff absenteeism.
Online veröffentlicht: 18. Oktober 2023
Gesehen am 07.05.2024